Silico substrate specificity in bmgt1 and bmgt2 genes of bacopa monniera glycosyltransferases online journal of bioinformatics - Sharma, Ranu; Ruby; Khan, Bashir Mohammad; Suresh, C.G. (Bioinformatics, 2011)

Genome-wide identification and tissue-specific expression analysis of UDP-glycosyltransferases genes confirm their abundance in cicer arietinum (chickpea) genome - Sharma, Ranu; Rawat, Vimal; Suresh, C. G. (Plos One, 2014)
UDP-glycosyltransferases (EC 2.4.1.x; UGTs) are enzymes coded by an important gene family of higher plants. They are involved in the modification of secondary metabolites, phytohormones, and xenobiotics by transfer of sugar moieties from an activated nucleotide molecule to a wide range of acceptors. This modification regulates various functions like detoxification of xenobiotics, hormone homeostasis, and biosynthesis of secondary metabolites. Here, we describe the identification of 96 UGT genes in Cicer arietinum (CaUGT) and report their tissue-specific differential expression based on publically available RNA-seq and expressed sequence tag data. This analysis has established medium to high expression of 84 CaUGTs and low expression of 12 CaUGTs. We identified several closely related orthologs of CaUGTs in other genomes and compared their exon-intron arrangement. An attempt was made to assign functional specificity to chickpea UGTs by comparing substrate binding sites with experimentally determined specificity. These findings will assist in precise selection of candidate genes for various applications and understanding functional genomics of chickpea.

Improved method for specificity annotation shows a distinct evolutionary divergence among the microbial enzymes of the cholylglycine hydrolase family - Panigrahi, Priyabrata; Sule, Manas; Sharma, Ranu; Ramasamy, Sureshkumar; Suresh, C. G. (Microbiology-SGM, 2014)
Bile salt hydrolases (BSHs) are gut microbial enzymes that play a significant role in the bile acid modification pathway. Penicillin V acylases (PVAs) are enzymes produced by environmental microbes, having a possible role in pathogenesis or scavenging of phenolic compounds in their microbial habitats. The correct annotation of such physiologically and industrially important enzymes is thus vital. The current methods relying solely on sequence homology do not always provide accurate annotations for these two members of the cholylglycine hydrolase (CGH) family as BSH/PVA enzymes. Here, we present an improved method [binding site similarity (BSS)-based scoring system] for the correct annotation of the CGH family members as BSH/PVA enzymes, which along with the phylogenetic information incorporates the substrate specificity as well as the binding site information. The BSS scoring system was developed through the analysis of the binding sites and binding modes of the available BSH/PVA structures with substrates glycocholic acid and penicillin V. The 198 sequences in the dataset were then annotated accurately using BSS scores as BSH/PVA enzymes. The dataset presented contained sequences from Gram-positive bacteria, Gram-negative bacteria and archaea. The clustering obtained for the dataset using the method described above showed a clear distinction in annotation of Gram-positive bacteria and Gram-negative bacteria Based on this clustering and a detailed analysis of the sequences of the CGH family in the dataset, we could infer that the CGH genes might have evolved in accordance with the hypothesis stating the evolution of diderms and archaea from the monoderms.

In-Silico analysis of binding site features and substrate selectivity in plant flavonoid-3-o glycosyltransferases (F3GT) through molecular modeling, docking and dynamics simulation studies - Sharma, Ranu; Panigrahi, Priyabrata; Suresh, C. G. (Plos One, 2014)
Flavonoids are a class of plant secondary metabolites that act as storage molecules, chemical messengers, as well as participate in homeostasis and defense processes. They possess pharmaceutical properties important for cancer treatment such as antioxidant and anti-tumor activities. The drug-related properties of flavonoids can be improved by glycosylation. The enzymes glycosyltransferases (GTs) glycosylate acceptor molecules in a regiospecific manner with the help of nucleotide sugar donor molecules. Several plant GTs have been characterized and their amino acid sequences determined. However, three-dimensional structures of only a few are reported. Here, phylogenetic analysis using amino acid sequences have identified a group of GTs with the same regiospecific activity. The structures of these closely related GTs were modeled using homologous GT structures. Their substrate binding sites were elaborated by docking flavonoid acceptor and UDP-sugar donor molecules in the modeled structures. Eight regions near the acceptor binding site in the N- and C-terminal domain of GTs have been identified that bind and specifically glycosylate the 3-OH group of acceptor flavonoids. Similarly, a conserved motif in the C-terminal domain is known to bind a sugar donor substrate. In certain GTs, the substitution of a specific glutamine by histidine in this domain changes the preference of sugar from glucose to galactose as a result of changed pattern of interactions. The molecular modeling, docking, and molecular dynamics simulation studies have revealed the chemical and topological features of the binding site and thus provided insights into the basis of acceptor and donor recognition by GTs.

Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation

Genome-wide identification and structure-function studies of proteases and protease inhibitors in cicer arietinum (chickpea) - Sharma, Ranu; Suresh, C. G. (Computers in Biology and Medicine, 2015)
Background: Proteases are a family of enzymes present in almost all living organisms. In plants they are involved in many biological processes requiring stress response in situations such as water deficiency, pathogen attack, maintaining protein content of the cell, programmed cell death, senescence, reproduction and many more. Similarly, protease inhibitors (PIs) are involved in various important functions like suppression of invasion by pathogenic nematodes, inhibition of spores-germination and mycelium growth of Alternaria alternata and response to wounding and fungal attack. As much as we know, no genome-wide study of proteases together with proteinaceous PIs is reported in any of the sequenced genomes till now. Methods: Phylogenetic studies and domain analysis of proteases were carried out to understand the molecular evolution as well as gene and protein features. Structural analysis was carried out to explore the binding mode and affinity of PIs for cognate proteases and prolyl oligopeptidase protease with inhibitor ligand. Results: In the study reported here, a significant number of proteases and PIs were identified in chickpea genome. The gene expression profiles of proteases and Pis in five different plant tissues revealed a differential expression pattern in more than one plant tissue. Molecular dynamics studies revealed the formation of stable complex owing to increased number of protein-ligand and inter and intramolecular protein-protein hydrogen bonds. Discussion: The genome-wide identification, characterization, evolutionary understanding, gene expression, and structural analysis of proteases and Pis provide a framework for future analysis when defining their roles in stress response and developing a more stress tolerant variety of chickpea. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Domain; Gene expression; Genome analysis; Homology modelling; Molecular docking; molecular dynamics simulation; Motif; Orthologs; Phylogeny